Current status of Belgica antarctica Jacobs, 1900 (Diptera: Chironomidae) distribution by the data of Ukrainian Antarctic Expeditions - Kovalenko, P.; Trokhymets, V.; Parnikoza, I.; Protsenko, Yu.; Salganskiy, O.; Dzhulai, A.; Dykyy, I.; Nabokin, M.; Kozeretska, I.; Gorobchyshyn, V. (Ukrainian Antarctic Journal, 2021)
Given the recent climate changes and their impact on the Antarctic Peninsula ecosystems, the emergence of invasive species, and increased tourism activity in this region, monitoring changes in the habitats of species native to the Antarctic Peninsula region is necessary. One such species is the Antarctic midge Belgica antarctica (Chironomidae). This insect is endemic to the Antarctic Peninsula and adjacent islands. Thorough studies of changes in the range of this species have not been performed in recent decades. In this study, we present the area of Belgica antarctica according to the collections of biological samples during 2007–2021 (XII, XIV, XVI, XXIV, and XXV Ukrainian Antarctic Expeditions). This Antarctic midge was recorded at 26 localities on the Antarctic Peninsula and 212 localities on 55 surrounding islands between 66°08′38.4′′ S, 65°43′37.1′′ W (Cape Evensen, Stresher Peninsula, opposite the Marie Island, west coast of Graham Land) and 62°11′44.7′′ S, 58°57′40.6′′ W (King George Island, South Shetland Islands) from south-west to north-east.